A Series of Mesoporous Rare‐Earth Metal–Organic Frameworks Constructed from Organic Secondary Building Units. Issue 4 (24th November 2020) - Lv, Xiu‐Liang; Feng, Liang; Wang, Kun‐Yu; Xie, Lin‐Hua; He, Tao; Wu, Wei; Li, Jian‐Rong; Zhou, Hong‐Cai
Abstract: Further development of metal–organic frameworks (MOFs) requires an establishment of hierarchical interaction within the framework. Herein, we report a series of mesoporous rare‐earth (RE) MOFs that are constructed from an unusual 12‐connected π‐stacked pyrene secondary building unit (SBU) and a typical 12‐connected RE6 cluster (RE=Eu, Y, Yb, Tb, Ce). The judicious design of a butterfly‐shape pyrene ligand with a tert ‐butyl substituent enables the formation of the disordered 12‐connected organic SBUs on its strong intermolecular π–π interactions. The assembly of 12‐connected inorganic cuboctahedron SBUs and 12‐connected organic distorted hexagonal prism SBUs generates an unprecedented network that can be further simplified into a 4, 4‐connected pts net linked from planar square and tetrahedra. This work provides fresh insights into the design and synthesis of frameworks constructed from coordinatively, covalently, and noncovalently linked building units. Abstract : A series of unprecedented mesoporous rare‐earth MOFs were constructed from pyrene‐based organic SBUs. The highly accessible Lewis acidic metal sites within mesopores and robust framework make PCN‐2020(Ce) an efficient catalyst for CO2 conversion.